2013
DOI: 10.1016/j.icarus.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Saturn’s thermal emission at 2.2-cm wavelength: Spatial distribution of ammonia vapor

Abstract: This work focuses on determining the latitudinal structure of ammonia vapor in Saturn's cloud layer near 1.5 bars using the brightness temperature maps derived from the Cassini RADAR (Elachi et al. [2004], Space Sci. Rev. 115, 71-110) instrument, which works in a passive mode to measure thermal emission from Saturn at 2.2-cm wavelength. We perform an analysis of five brightness temperature maps that span epochs from 2005 to 2011, which are presented in a companion paper by Janssen et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…In fact, studies with the Very Large Array (VLA) show depleted ammonia with respect to saturation for all four giant planets in the Solar System (de Pater ;Massie 1985;de Pater et al 2001). The same depletion of ammonia is also observed after Saturn's Giant Storm Laraia et al 2013) and in the smaller storm in Saturn's southern hemisphere (Dyudina et al 2007). Li;…”
Section: Interpretation Of Galileo Probe Resultsmentioning
confidence: 84%
“…In fact, studies with the Very Large Array (VLA) show depleted ammonia with respect to saturation for all four giant planets in the Solar System (de Pater ;Massie 1985;de Pater et al 2001). The same depletion of ammonia is also observed after Saturn's Giant Storm Laraia et al 2013) and in the smaller storm in Saturn's southern hemisphere (Dyudina et al 2007). Li;…”
Section: Interpretation Of Galileo Probe Resultsmentioning
confidence: 84%
“…The warming contributes to the re-evaporation of the condensates (the obscuring white aerosols), and the descent of the dry air in cells is expected to cause further depletion of other tropospheric species -ammonia, phosphine and H 2 S -which decrease in abundance with height, in addition to those that have already been precipitated. This compensating subsidence may explain the observed NH 3 depletion to several bars over much of Jupiter (de Pater et al, 2001;Showman and de Pater, 2005), as well as the observed dearth of NH 3 opacity in the aftermath of Saturn's springtime storm Laraia et al, 2013). After the downdrafts, the remaining atmosphere of the SEB would be unsaturated and stable.…”
Section: Vertical Structure Of Convective Complexesmentioning
confidence: 93%
“…Perturbations in the troposphere were much more subdued, although Achterberg et al (2014) reported an increase of about 3 K in the far-IR (20-200 µm, probing the upper troposphere near 400 mbar) thermodynamic temperature at the storm's latitude. In addition, 2.2-cm thermodynamic temperatures measured by the Cassini spacecraft three months into the storm were observed to increase more significantly (from 148 K to 166 K) at the storm latitude, likely due to a strong reduction in the relative humidity of ammonia there (Laraia et al 2013). Although this information is not quite sufficient to quantitatively estimate the change of the disc-averaged continuum thermodynamic temperature at the storm's epoch, it seems clear that if anything, the effect of the storm would be an increase in these continuum temperatures.…”
Section: Saturnmentioning
confidence: 97%